Negative electrode material for secondary battery, secondary battery, and method for producing negative electrode material for secondary battery

By using the composite material of the non -fixed material phase and silicate phase in the negative electrode material of the secondary battery, the problem of large irreversible capacity in the existing technology is solved, and the stable capacity is reduced and the efficiency of charge and discharge is improved.

CN119366004APending Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046712.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, the irreversible capacity of the negative electrode material for secondary batteries is relatively large and it is difficult to effectively reduce.

Method used

A composite material containing an amorphous material phase and a silicate phase is used as the negative electrode material. The silicate phase is dispersed in the amorphous material phase. The amorphous material phase containing Si, O and C and the silicate phase containing the element M are used. .

Benefits of technology

By dispersing the silicate phase containing element M in the amorphous material phase, the irreversible capacity can be stably reduced and the charge and discharge efficiency and cycle characteristics can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366004A_ABST
    Figure CN119366004A_ABST
Patent Text Reader

Abstract

A negative electrode material for a secondary battery is provided with a composite material. The composite material comprises an amorphous material phase and a silicate phase dispersed within the amorphous material phase. The amorphous material phase contains Si, O, and C. The silicate phase contains at least one element M selected from the group consisting of Li, Na, K, Mg, Ca, B and Al.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode material for a secondary battery, a secondary battery, and a method for producing the negative electrode material for a secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries, especially lithium-ion secondary batteries, have high voltage and high energy density, and are therefore highly anticipated as power sources for small-scale consumer applications, power storage devices, and electric vehicles. In the case of requiring batteries to have high energy density, silicon (Si)-containing materials that alloy with lithium are expected to be used as negative electrode active materials with high theoretical capacity density.

[0003] Patent document 1 proposes a method for producing porous amorphous carbon, which is characterized in that one or more organic silicon compounds selected from cross-linkable silanes and siloxanes are impregnated into a porous resin, and after a cross-linked product of the above-mentioned organic silicon compounds is formed in the porous resin, it is heated at a temperature of 650 to 1350° C. in a non-oxidizing gas to react, thereby obtaining an amorphous material containing silicon, carbon and oxygen as constituent elements and having oxidation resistance.

[0004] Prior Art Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2007-115548 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The amorphous material obtained by the production method of Patent Document 1 has a large irreversible capacity.

[0008] Means for solving problems

[0009] In view of the above, one aspect of the present disclosure relates to a negative electrode material for a secondary battery, which has a composite material, wherein the composite material includes an amorphous material phase and a silicate phase, the silicate phase is dispersed in the amorphous material phase, the amorphous material phase includes Si, O and C, and the silicate phase contains an element M, and the element M is at least one selected from Li, Na, K, Mg, Ca, B and Al.

[0010] Another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode includes the negative electrode material for a secondary battery.

[0011] Another aspect of the present disclosure relates to a method for manufacturing a negative electrode material for a secondary battery, which includes a step of obtaining a raw material mixture and a step of firing the raw material mixture to generate a composite material, wherein the raw material mixture includes a first polymer, a material constituting an active phase that reacts with Li, and a compound containing an element M, wherein the first polymer is an organic silicon polymer containing Si, O and C, and the composite material includes an amorphous material phase, the active phase and a silicate phase, wherein the active phase and the silicate phase are respectively dispersed in the amorphous material phase, the amorphous material phase contains Si, O and C, and the silicate phase and the amorphous material phase each independently contain the element M, and the element M is at least one selected from Li, Na, K, Mg, Ca, B and Al.

[0012] Effects of the Invention

[0013] According to the present disclosure, the irreversible capacity of a negative electrode material for a secondary battery can be reduced.

[0014] The novel features of the present invention are described in the appended claims, and the present invention, both in terms of technical composition and content, combined with other objects and features of the present invention, will be better understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a cross-sectional SEM image showing an example of a composite material included in the negative electrode material according to one embodiment of the present disclosure.

[0016] Figure 2 This is a cross-sectional view schematically showing an example of a negative electrode material according to an embodiment of the present disclosure.

[0017] Figure 3 This is a schematic perspective view in which a portion of a secondary battery according to an embodiment of the present disclosure is cut away. DETAILED DESCRIPTION

[0018] Hereinafter, the embodiments of the present disclosure are illustrated, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values, materials, etc. are sometimes illustrated, but other numerical values, materials, etc. may also be applied as long as the effects of the present disclosure can be obtained. In addition, the constituent elements other than the characteristic parts of the present disclosure may be constituent elements of known secondary batteries. In this specification, when "a range of numerical values ​​A to numerical values ​​B" is mentioned, the range includes numerical values ​​A and numerical values ​​B. In the following description, when a lower limit and an upper limit are illustrated for numerical values ​​of specific physical properties or conditions, any of the illustrated lower limits and any of the illustrated upper limits may be arbitrarily combined, as long as the lower limit is not above the upper limit.

[0019] The present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims. In other words, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims may be combined as long as no technical contradiction occurs.

[0020] The negative electrode material for secondary batteries according to the embodiments of the present disclosure comprises a composite material comprising an amorphous material phase and a silicate phase. The composite material may be provided in the form of a block, a sheet, a powder containing a plurality of particles, etc. Hereinafter, the particles of the composite material are also referred to as "composite particles".

[0021] The silicate phase is dispersed in the amorphous material phase containing Si, O and C. The silicate phase contains element M (cationic substance). Element M is at least one selected from Li, Na, K, Mg, Ca, B and Al. The silicate phase is composed of silicate. Silicate is a compound containing silicon element (Si) and anions.

[0022] By including a silicate phase containing an element M having a small irreversible capacity in the amorphous material phase and replacing a portion of the amorphous material with the silicate phase, the large irreversible capacity generated by the amorphous material phase can be reduced. By dispersing a silicate phase containing the element M in the amorphous material phase, the effect of reducing the irreversible capacity can be stably obtained.

[0023] From the viewpoint of high capacity, the composite material preferably contains an active phase that reacts with Li. The active phase is dispersed in the amorphous material phase together with the silicate phase. In this case, in the secondary battery, a high initial capacity can be obtained, and the charge and discharge efficiency is improved, and excellent charge and discharge cycle characteristics can be obtained.

[0024] The amorphous material phase and the silicate phase are formed of a material having a smaller capacity per unit mass (mAh / g) than the active phase. The amorphous material phase and the silicate phase have a smaller or no volume change caused by charge and discharge than the active phase. The amorphous material phase with the silicate phase dispersed inside alleviates the stress caused by the expansion and contraction of the active phase. By dispersing the active phase in the amorphous material phase, the side reaction between the active phase and the electrolyte is suppressed.

[0025] The composite material may have an island-in-sea structure. In the island-in-sea structure, the silicate phase (or the silicate phase and the active phase) constitutes the island portion, and the amorphous material phase constitutes a continuous sea portion or matrix. In the case where the composite material is a powder, in a particle of the composite material, a plurality of island portions are dispersed in the sea portion. The island portion is preferably buried in the sea portion. In some island portions, at least a portion of the surface of the island portion may be exposed without being covered by the sea portion.

[0026] (Amorphous Material Phase)

[0027] The amorphous material phase contains Si (silicon), O (oxygen) and C (carbon). The amorphous material phase forms a compound in which Si, O and C are randomly bonded by covalent bonds. The amorphous material phase has, for example, a Si-OC bond (covalent bond). That is, the amorphous material phase is not a simple mixture or a simple complex of multiple compounds (SiO, SiC, etc.). The amorphous material phase is a phase with an unspecified crystalline structure. The amorphous material phase can form a single phase that does not have an interface between different materials that a composite of two or more materials has. Because the amorphous material phase contains Si, O and C as essential components and is a phase with an unspecified crystalline structure, the hardness of the composite material becomes higher, and it also has elasticity or softness that alleviates the stress caused by the expansion and contraction of the active phase.

[0028] Preferably, in the cross section of the composite material, the amorphous material phase does not have substantial grain boundaries. By making the amorphous material phase a continuous structure without substantial grain boundaries, the hardness of the composite material becomes higher, and the phenomenon of electrolyte infiltration into the grain boundaries becomes less, the side reactions associated with the decomposition of the electrolyte are suppressed, and the material becomes less likely to deteriorate. In this case, the composite material can be formed into primary particles. However, the amorphous material phase may also have a small amount of grain boundaries. The state that the amorphous material phase does not substantially have grain boundaries can be confirmed by a cross-sectional SEM image of the composite material. In a field of view of 500nm 2 In the cross-sectional SEM image of the composite material at the time of , if the total length of the grain boundaries in the amorphous material phase is less than 1 nm, it can be said that the amorphous material phase does not substantially have grain boundaries. Preferably, the same measurement is performed on any 10 composite particles, and the measured values ​​are averaged to obtain the length of the grain boundaries.

[0029] From the viewpoint of reducing the irreversible capacity, it is preferred that the amorphous material phase contains an element M (selected from at least one of Li, Na, K, Mg, Ca, B and Al). In this case, the amorphous material phase and the silicate phase may contain the same type of element M as each other, or may contain different types of element M from each other. Among them, it is more preferred that the amorphous material phase contains at least Li as the element M. In the case where the element M contained in the amorphous material phase is an element other than Li, during the charge and discharge of a lithium ion secondary battery having a negative electrode containing a composite material, elements other than Li are replaced by Li, and Li ions are irreversibly captured in the amorphous material phase, whereby the capacity is sometimes reduced. In the case where the element M contains Li, the above-mentioned capacity reduction can be suppressed.

[0030] In the amorphous material phase, the general formula (1): M a SiO x N y C zWhen expressed, the general formula (1) satisfies, for example, 0≤a≤4, 0.1≤x≤2.5, 0≤y≤0.5, and 0<1-0.5x-0.75y<z≤6. M is at least one selected from Li, Na, K, Mg, Ca, B and Al. Such a composition is empirically determined based on the composition of the amorphous material phase produced by the production method described later. During charge and discharge, Li can be captured as irreversible capacity.

[0031] From the viewpoint of reducing the irreversible capacity, the amorphous material phase preferably contains the element M. It is preferred that the element M (e.g., Li) is doped into the amorphous material phase during the preparation of the composite material (before the initial charge). That is, in the general formula (1), it is preferred that 0<a≤4 is satisfied. In addition, a in the general formula (1) is more preferably greater than 0.1, and further preferably greater than 1. In addition, when M is Li, from the viewpoint of easily suppressing the dissolution of the amorphous material phase into water, a in the general formula (1) can be less than 2.

[0032] In the general formula (1), the range of z, which represents the atomic ratio of C to Si, can be 0.1≤z≤6, 0.5≤z≤4, or 0.5≤z≤3. By controlling the amount of carbon contained in the amorphous material phase within the above range, it is difficult to form Si-O-Li bonds, the irreversible capacity of the composite material is reduced, and the amorphous material phase itself has capacity, which is conducive to high capacity. In the general formula (1), M is preferably Li.

[0033] The composition of the amorphous material phase (quantitative analysis of each element in the composite material) can be performed by scanning electron microscopy (SEM)-energy dispersive X-ray (EDX) analysis. In SEM-EDX analysis, the cross section of the composite material is observed using SEM, and element mapping analysis is performed using EDX. The observation magnification is preferably 2000 to 20000 times. It is preferred to perform image analysis on the area 1 μm or more inside the cross-sectional edge of the composite material particle. In the image analysis, the element content ratio (i.e., composition) can be calculated using image analysis software. The same measurement can be performed on any 10 particles, and the measured values ​​can be averaged to obtain the composition. The maximum diameter of the measured particle is preferably 5 μm or more. The cross section of the composite material particle can be formed, for example, by filling the composite material in a thermosetting resin and curing it, using a cross-section polisher (CP), or by disassembling the battery to remove the negative electrode, immersing the negative electrode in a thermosetting resin and curing it, and forming it in the cross section of the negative electrode.

[0034] Preferred measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0035] Processing equipment: IB-19520CCP (cross-section polishing machine) manufactured by NEC Corporation

[0036] Processing conditions: Acceleration voltage 6kV

[0037] Current value: 150~180μA

[0038] Vacuum degree: 5×10 -4 ~2×10 -3 Pa

[0039] Measuring apparatus: JSM-7900F manufactured by JEOL Ltd. (field emission scanning electron microscope), Ultim Extreme manufactured by Oxford Instruments Ltd. (EDX detector)

[0040] Accelerating voltage during analysis: 3kV

[0041] In the C1s spectrum obtained by the X-ray photoelectron spectroscopy (XPS) of the composite material, a variety of C1s peaks contained in the amorphous material phase are observed. For example, C1s peaks belonging to Si-C bonds, Si-OC bonds, CO bonds, CC bonds, etc. are observed. The presence of such peaks indicates that the amorphous material phase contains a considerable amount of regions other than oxides. Among them, the C1s peak belonging to the CC bond is a characteristic peak of the composite material disclosed in the present invention, indicating that the amorphous material phase contains a region composed of carbon. The peak from the CC bond is observed, for example, near 284.8 eV.

[0042] Here, the ratio of the peak area Sx derived from the CC bond to the total area St of all C1s peaks is, for example, 2% or more, 3% or more, or 5% or more. In addition, the ratio of Sx to St is, for example, 90% or less, 70% or less, or 20% or less. The ratio of Sx to St may be 2% or more and 90% or less, or 2% or more and 20% or less.

[0043] The ratio of the total of the peak area Sy derived from C—Si bonds and the peak area Sz derived from CO—Si bonds to the total area St may be 50% or more, 60% or more, or 70% or more.

[0044] In XPS of composite materials, powder of the composite material is used as a sample, and analysis is performed from the sample surface along the depth direction (10 to 100 nm) of the composite material to analyze the internal state of the composite material.

[0045] Preferred XPS measurement conditions are shown below.

[0046] Measuring device: PHI5000 manufactured by ULVAC-PHI

[0047] X-ray used: Monochromatic Al-Kα, 25W, 15kV

[0048] Vacuum degree: 5×10-7 Pa

[0049] In the 13C NMR measurement of the composite material, the peak derived from the CC bond characteristic of the composite material of the present disclosure is also observed. The peak area Sv of the spectrum above 9 ppm and below 30 ppm obtained by the 13C-NMR measurement of the composite material can be, for example, 10% to 90% of the entire spectrum area.

[0050] Preferred 13C NMR measurement conditions are shown below.

[0051] Measuring device: JNM-ECZ-600

[0052] Magnetic field strength: 14.1T

[0053] MAS-speed: 15kHz

[0054] (Silicate phase)

[0055] The silicate phase contains at least one element M selected from Li, Na, K, Mg, Ca, B and Al. Among them, it is preferred that the silicate phase contains at least Li as the element M. When the element M contained in the silicate phase is an element other than Li, during the charge and discharge of a lithium ion secondary battery having a negative electrode containing a composite material, the element other than Li is replaced by Li, and the Li ions are irreversibly captured in the silicate phase, thereby sometimes reducing the capacity. When the element M contains Li, the above-mentioned capacity reduction can be suppressed.

[0056] The silicate phase is composed of, for example, the elements M, Si and O. From the viewpoint of reducing the irreversible capacity and chemical stability, the silicate phase may contain at least one selected from Li4SiO4, Li2SiO3 and Li2Si2O5. Among them, from the viewpoint of reducing the irreversible capacity of the silicate phase and inhibiting the dissolution of the amorphous material phase into water, it is preferred that the silicate phase contains Li2Si2O5.

[0057] When the silicate phase is in a particle form, the average particle size of the silicate phase can be greater than 10 nm and less than 100 μm, or greater than 100 nm and less than 10 μm. The particle form refers to a state in which the silicate phase (or island portion) has a particle form. There is no particular limitation on the shape of the particle, and the ratio A / B of the maximum diameter A of the particle to the maximum width B in the direction perpendicular to the maximum diameter can be, for example, greater than 1 and less than 20, greater than 1 and less than 10, greater than 1 and less than 5, or greater than 1 and less than 3. A / B can be calculated as the average value of any 10 silicate phases (or island portions) in particle form. The smaller the average particle size of the silicate phase, the more conducive it is to relieving the stress of expansion and contraction during charging and discharging.

[0058] The average particle size of the silicate phase is measured using a cross-sectional image of the composite material obtained by SEM. The average particle size of the silicate phase is obtained by averaging the maximum diameters of any 100 silicate phases.

[0059] The composite material may have voids inside the amorphous material phase. In this case, the silicate phase may be exposed on the inner wall surface of the void. Due to the presence of the void, the stress caused by the expansion and contraction of the active phase is easily alleviated. Depending on the type of compound containing element M used in the first step of the method for manufacturing the negative electrode material described later, voids are easily formed near the silicate phase, and the voids are easily formed in a manner that the silicate phase is exposed on the inner wall surface. The silicate phase is exposed on the inner wall surface of the void, and the exposure of the active phase on the inner wall surface of the void can be reduced accordingly. In the case where the void is not completely enclosed in the composite material (communicated with the outside of the composite material), the exposure of the active phase that may contact the electrolyte can be reduced.

[0060] Here, Figure 1 This is a cross-sectional SEM image (backscattered electron image) showing an example of a composite material included in the negative electrode material according to one embodiment of the present disclosure.

[0061] Figure 1 The cross section of the composite particle included in the negative electrode material A1 of Example 1 described later is shown. Figure 1 In the figure, the parts with symbols a, b and c are the amorphous material phase, the silicate phase and the void, respectively. The silicate phase b is exposed on the inner wall surface of the void c. Figure 1 The composite particles shown do not include an active phase, but the composite particles may also include an active phase dispersed within an amorphous material phase.

[0062] The composition of the silicate phase can be determined by the above-mentioned SEM-EDX analysis. Since the silicate phase has high crystallinity, the composition of the silicate phase can also be confirmed by X-ray diffraction (XRD).

[0063] (Active phase)

[0064] The active phase can be composed of a material that can undergo an electrochemical reversible reaction with Li during charge and discharge. The material constituting the active phase includes, for example, at least one selected from metals and intermetallic compounds. In addition, the material constituting the active phase may be a silicon compound such as silicon carbide, a composite oxide such as a lithium-titanium composite oxide, etc. The active phase may be used alone or in combination of two or more.

[0065] When a metal is used as a material constituting the active phase, the metal may be at least one selected from Si, Sn, Ti, Al and Mg. Among them, Si and Sn have high capacity, and Si is particularly inexpensive and is therefore preferred.

[0066] In the case of using an intermetallic compound as a material constituting the active phase, the intermetallic compound may be selected from CrSi2, MnSi2, FeSi2, CoSi2, NiSi2, LiNiSn and MnSi2. x At least one of Si (M is at least one selected from Li, Na, K, Mg, Ca, B and Al, and satisfies 0<x<5).

[0067] The above-mentioned intermetallic compound may contain the element M from the compound containing the element M used in making the composite material. The element M from the compound containing the element M may be doped into the active phase during the preparation of the composite material. When the material constituting the active phase contains Si, the above-mentioned M may be formed as an intermetallic compound. x Four.

[0068] The content of the active phase in the composite material can be appropriately controlled. From the viewpoint of high capacity, the content of the active phase in the composite material is preferably as much as possible. On the other hand, from the viewpoint of relieving the stress caused by the expansion and contraction of the active phase and suppressing the side reaction of the active phase with the electrolyte, the composite material needs to contain a certain amount of amorphous material phase. The content of the active phase in the composite material is, for example, more than 20% by mass and less than 95% by mass, and can also be more than 35% by mass and less than 75% by mass.

[0069] When the active phase is silicon, the content of the Si phase contained in the composite material can be measured by Si-NMR.

[0070] When the active phase is in a particle shape, the average particle size of the active phase can be greater than 1 nm and less than 1000 nm. The particle shape refers to the state in which the active phase (or island portion) has a particle shape. There is no particular limitation on the shape of the particle. The ratio A / B of the maximum diameter A of the particle to the maximum width B in the direction perpendicular to the maximum diameter can be, for example, greater than 1 and less than 20, greater than 1 and less than 10, greater than 1 and less than 5, or greater than 1 and less than 3. A / B can be calculated as the average value of any 10 active phases (or island portions) having a particle shape. The smaller the average particle size of the active phase, the easier it is to ease the stress caused by the expansion and contraction of the active phase, and the easier it is to suppress the deterioration caused by the cracking of the active phase itself. On the other hand, the larger the average particle size of the active phase, the easier it is to suppress the side reaction of the active phase with the electrolyte. The average particle size of the active phase can be less than 200 nm, less than 100 nm, or less than 50 nm.

[0071] The average particle size of the active phase is measured using a cross-sectional image of the composite material obtained by SEM. The average particle size of the active phase is obtained by averaging the maximum particle sizes of any 100 active phases.

[0072] (Carbon material)

[0073] In addition to the composite material, the negative electrode material may also contain at least one carbon material selected from graphite (natural graphite, artificial graphite), hard carbon and soft carbon. In addition, the carbon material may be composited with an amorphous material. For example, a silicate phase (or a silicate phase and an active phase) may be dispersed in a composite material of a carbon material and an amorphous material phase.

[0074] Compared with the active phase, the carbon material has a small degree of expansion and contraction during charge and discharge, so it is easy to improve the cycle characteristics of the battery by using it in combination with the composite material. The proportion of the carbon material in the total of the composite material and the carbon material can be, for example, 70% by mass or more and 99% by mass or less, 85% by mass or more and 95% by mass or less, or 90% by mass or more and 95% by mass or less. Thus, it is easy to take into account both high capacity and better cycle characteristics.

[0075] (Conductive layer)

[0076] From the viewpoint of improving conductivity, the negative electrode material may have a conductive layer covering the surface of the composite material. The conductive layer may contain a conductive carbon material. The thickness of the conductive layer is preferably thin enough not to substantially affect the average particle size of the composite particles. The thickness of the conductive layer is, for example, 1 nm or more and 10 nm or less.

[0077] The conductive layer is formed by mixing a raw material of a conductive carbon material and a composite material, firing the mixture, and carbonizing the raw material of the conductive carbon material. As the raw material of the conductive material, for example, coal tar pitch or coal tar pitch, petroleum asphalt, phenolic resin, etc. can be used. The firing of the mixture of the raw material of the conductive carbon material and the composite material is carried out, for example, in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.). The firing temperature is, for example, not less than 450°C and not more than 1000°C. The firing time is, for example, not less than 1 hour and not more than 10 hours.

[0078] Figure 2 This is a cross-sectional view schematically showing an example of a negative electrode material according to an embodiment of the present disclosure.

[0079] The negative electrode material 20 includes a composite particle 21 and a conductive layer 25 covering the surface of the composite particle 21. The composite particle 21 includes an amorphous material phase 22, an active phase 23, and a silicate phase 24. The composite particle 21 has a sea-island structure in which the active phase 23 and the silicate phase 24 are dispersed in a matrix of the amorphous material phase 22. Figure 2 As shown, voids 26 may be formed in the amorphous material phase 22. The silicate phase 24 may be exposed on the inner wall surface of the voids 26.

[0080] [Method for producing negative electrode material for secondary battery]

[0081] A method for producing a negative electrode material for a secondary battery including a composite material in which a silicate phase and an active phase are dispersed in an amorphous material phase includes, for example, the following first and second steps.

[0082] (i) Step 1

[0083] The first step is a step of obtaining a raw material mixture containing a first polymer, a material constituting an active phase that reacts with Li, and a compound containing the element M.

[0084] (First polymer)

[0085] The first polymer is a raw material of an amorphous material phase containing Si, O and C, and contains Si, O and C. In addition, a part of the first polymer (Si, O) is used to form a silicate phase together with a compound containing element M. The first polymer may be an organosilicon polymer.

[0086] The organosilicon polymer can be an organosilicon polymer used as a ceramic precursor polymer. The ceramic precursor polymer can generate ceramics by controlling the firing conditions. Most organosilicon polymers have thermoplasticity and are liquid when heated in the subsequent second step. The organosilicon polymer can be a polymer that is liquid at room temperature (25°C to 35°C). By using a first polymer that is liquid at room temperature or when heated, an amorphous material phase that does not substantially have grain boundaries can be generated, and a composite material with high particle destructive strength can be obtained.

[0087] Silicone polymers are generally soluble in organic solvents and are easy to handle. In the first step, in order to obtain a uniform raw material mixture, the silicone polymer can be used in a state of being mixed with an organic solvent. Most of the organic solvent volatilizes during the calcination in the second step. When the silicone polymer is solid at room temperature, the silicone polymer can be dissolved in an organic solvent for use. From the viewpoint of easily obtaining a uniform paste-like raw material mixture, the kinematic viscosity of a liquid silicone polymer (or a mixture of a silicone polymer and an organic solvent) at room temperature is, for example, 0.1 mm 2 / s or more and 500mm 2 / s or less.

[0088] The first polymer may be, for example, polysiloxane, polycarbosilane, polysilazane, polyorganopolysiloxane, polymetallosiloxane, polyborosiloxane, polycarbosilazane, etc. These may be used alone or in combination of two or more. For example, at least one selected from polysiloxane, polycarbosilane, and polysilazane may be used.

[0089] Polysiloxane is a polymer compound with Si-O bond as the basic skeleton. Polycarbosilane is a polymer compound with Si-C bond as the basic skeleton. Polysilazane is a polymer compound with Si-N bond as the basic skeleton. The molecules of these polymer compounds can be linear, branched, or three-dimensional. Examples of polysiloxane include silicone resins and silicone oils. Examples of silicone resins include Shin-Etsu Chemical Co., Ltd.'s trade name "KR-112".

[0090] The polysiloxane has, for example, a repeating unit represented by the following formula (2).

[0091] Formula (2):

[0092] Polycarbosilane has, for example, a repeating unit represented by the following formula (3).

[0093] Formula (3):

[0094] Polysilazane has, for example, a repeating unit represented by the following formula (4).

[0095] Formula (4):

[0096] These first polymers can form an amorphous material phase represented by the general formula (1).

[0097] In formulas (2) to (4), R 1 and R 2 Each independently represents, for example, a hydrogen atom or an organic group having 1 to 8 carbon atoms. The organic group includes a hydrocarbon group having a substituent (or a functional group) and a hydrocarbon group having no substituent (or a functional group). The functional group may be a hydroxyl group, a cyano group, an amino group, etc., without particular limitation. The hydrocarbon group may be, for example, an alkyl group, a vinyl group, an alkoxy group, an aryl group, an aryloxy group, a keto group, a carboxyl group, an ester group, etc. The multiple repeating units of the first polymer may have the same structure or different structures. That is, in the multiple repeating units of the first polymer, R 1 and R 2 They can be the same or different.

[0098] Examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, pentyl, and hexyl. Examples of the aryl group include phenyl, benzyl, and tolyl. Examples of the aryloxy group include phenoxy. Examples of the alkoxy group include oxyalkyl groups having 1 to 8 carbon atoms. Examples of the ester group include condensation groups of alcohols having 1 to 8 carbon atoms and carboxylic acids having 1 to 8 carbon atoms. For example, R 1 and R 2 Each independently may be phenyl, methyl, ethyl, or the like.

[0099] The weight average molecular weight (Mw) of the first polymer may be, for example, 1,000 to 100,000, 1,000 to 10,000, or 2,000 to 10,000.

[0100] (Material constituting the active phase)

[0101] As the material constituting the active phase, particles of the above-mentioned materials (hereinafter also referred to as "active particles") can be used. The active particles can be nanoparticles. The average particle size of the active particles can be greater than 1 nm and less than 1000 nm, less than 200 nm, less than 100 nm, or less than 50 nm. As active particles, for example, nanoparticles of silicon can be used.

[0102] The average particle size of the active particles is measured using a cross-sectional image of the composite material obtained by SEM. The average particle size of the active particles is obtained by averaging the maximum diameters of any 100 active particles.

[0103] In the raw material mixture, the amount of the material constituting the active phase relative to 100 parts by mass of the first polymer can be appropriately set according to the desired proportion of the active phase of the composite material, for example, from 20 parts by mass to 250 parts by mass, or from 50 parts by mass to 200 parts by mass.

[0104] (Compounds containing element M)

[0105] The element M is at least one selected from Li, Na, K, Mg, Ca, B and Al. The compound containing the element M preferably contains at least Li as the element M. In this case, in the second step, a composite material in which the amorphous material phase and the silicate phase each contain at least Li as the element M can be generated.

[0106] The compound containing element M contributes to the formation of a silicate phase containing element M and doping of element M into the amorphous material phase. In the second step, the silicate phase containing element M is formed with particles of the compound containing element M as cores. Si in the silicate phase is supplied by the first polymer around the particles of the compound containing element M. Anionic substances (e.g., O) of the silicate phase are supplied by the compound containing element M and / or the first polymer. A portion of element M is also supplied to the amorphous material phase formed by firing.

[0107] Examples of the compound containing the element M include salts formed by anions of carbonic acid or carboxylic acid (formic acid, acetic acid, benzoic acid, etc.) and cations of the element M. The compound containing the element M is, for example, at least one selected from lithium carbonate, lithium formate, lithium acetate, and lithium benzoate.

[0108] Among them, the compound containing element M is preferably lithium carbonate. In the case of lithium carbonate, during the firing of the second step, CO2 gas is generated along with the decomposition of lithium carbonate, thereby forming voids in the amorphous material phase. In addition, since the silicate phase is formed based on the particles of lithium carbonate, voids are easily formed near the silicate phase. Voids are easily formed so that the silicate phase is exposed on the inner wall surface.

[0109] The compound containing the element M can be used in the form of powder (particles). The maximum diameter of the particles of the compound containing the element M is, for example, in the range of 0.01 μm or more and 100 μm or less.

[0110] In the raw material mixture, the mixing ratio of the first polymer and the compound containing the element M can be appropriately adjusted according to the ratio of the silicate phase dispersed in the amorphous material phase. In the raw material mixture, the molar ratio M / Si of the element M derived from the compound containing the element M to Si derived from the first polymer can be 0.01 to 5 or more, or 0.1 to 2 or less.

[0111] (ii) Second step

[0112] The second step is a step of firing the raw material mixture to generate a composite material. The composite material includes an amorphous material phase, an active phase and a silicate phase. The active phase and the silicate phase are respectively dispersed in the amorphous material phase. The amorphous material phase includes Si, O and C. The silicate phase and the amorphous material phase each independently contain the element M.

[0113] The raw material mixture containing the first polymer, the material constituting the active phase, and the compound containing the element M is in a paste-like (or slurry-like) state with fluidity at room temperature, or at least passes through a state with fluidity during heating for firing. Thus, during firing in the second step, most of the surfaces of the material constituting the active phase and the compound containing the element M are covered with the first polymer with fluidity. In order to obtain a dense composite material in the second step, it is preferred to use a raw material mixture in this state.

[0114] By including a compound containing the element M in the raw material mixture, a silicate phase containing the element M can be formed, and the amorphous material phase can be doped with the element M. Thus, a composite material having a small irreversible capacity can be obtained.

[0115] The raw material mixture can be calcined at a temperature of, for example, 600° C. to 1000° C. in an inert atmosphere. The inert atmosphere can be a reduced pressure atmosphere or an inert gas flow. The inert gas can use argon, nitrogen, helium, etc. The calcination time is as long as the carbon atoms contained in the first polymer are fully carbonized. The composite material obtained after calcination is a solid without fluidity. By pulverizing the composite material, a composite material in a powder state is generated.

[0116] In the step of obtaining the raw material mixture, the raw material mixture may contain a second polymer that is carbonized together with carbon atoms in the first polymer when the raw material mixture is fired. The second polymer may be contained in the mixture as a raw material of at least one selected from graphite (natural graphite, artificial graphite), hard carbon and soft carbon.

[0117] The second polymer is not particularly limited, but is preferably a material having excellent compatibility with the first polymer. The second polymer may be, for example, at least one selected from polyethylene resin, polyimide resin, polyacrylonitrile, acrylic resin, and polyolefin resin.

[0118] [Secondary battery]

[0119] The secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes the negative electrode material for a secondary battery.

[0120] (negative electrode)

[0121] The negative electrode, for example, comprises a sheet-shaped negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector. The negative electrode mixture layer refers to a negative electrode mixture formed in a layer or film form. The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive auxiliary agent, a thickener, etc. as an optional component. The negative electrode active material includes a negative electrode material for a secondary battery.

[0122] The negative electrode mixture layer can be formed, for example, by applying a negative electrode slurry in which a negative electrode mixture is dispersed in a dispersion medium onto the surface of a negative electrode current collector and drying the slurry. The dried coating film can be rolled as necessary.

[0123] As the negative electrode current collector, a nonporous conductive substrate (metal foil, etc.) or a porous conductive substrate (grid, net, punching plate, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, and the like.

[0124] As the binder, resin materials can be used, for example, fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide resins such as polyimide and polyamide-imide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These can be used alone or in combination of two or more.

[0125] As the conductive auxiliary agent, for example, carbon black such as acetylene black, carbon nanotubes (hereinafter also referred to as CNT), metal fibers, carbon fluoride, metal powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, organic conductive materials such as benzene derivatives, etc. can be exemplified. These can be used alone or in combination of two or more.

[0126] (positive electrode)

[0127] The positive electrode contains a positive electrode active material that can electrochemically absorb and release lithium ions. The positive electrode, for example, includes a positive electrode collector and a positive electrode mixture layer formed on the surface of the positive electrode collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry formed by dispersing a positive electrode mixture in a dispersion medium on the surface of the positive electrode collector and drying it. The dried coating can be rolled as needed. The positive electrode mixture contains a positive electrode active material as an essential component, and can contain a binder, a conductive agent, etc. as an optional component.

[0128] As the positive electrode active material, for example, a lithium-containing composite oxide can be used. For example, Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2-b M bO4, LiMPO4, Li2MPO4F (M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B). Wherein, a = 0 to 1.2, b = 0 to 0.9, c = 2.0 to 2.3. In addition, the value a representing the molar ratio of lithium increases or decreases according to charge and discharge.

[0129] As the binder and the conductive agent, the same substances as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0130] The shape and thickness of the positive electrode current collector can be selected based on the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0131] (Electrolytes)

[0132] The electrolyte has lithium ion conductivity and can be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0133] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, well-known materials in all-solid lithium-ion secondary batteries, etc. (such as oxide solid electrolytes, sulfide solid electrolytes, halogen-based solid electrolytes, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be cited.

[0134] The electrolyte solution contains a solvent and an electrolyte salt. As the solvent, a non-aqueous solvent or water can be used. In the case of a lithium ion secondary battery, the electrolyte salt contains at least a lithium salt.

[0135] The concentration of the lithium salt in the electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte having excellent ion conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0136] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be mentioned. As chain carboxylates, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.

[0137] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , lower aliphatic carboxylic acid lithium, LiCl, LiBr, LiI, borates, imide salts, etc. The lithium salt may be used alone or in combination of two or more.

[0138] The electrolyte solution may further contain additives. Examples of the additives include vinylene carbonate (VC), fluoroethylene carbonate (FEC), and vinyl ethyl carbonate (VEC).

[0139] (Diaphragm)

[0140] Usually, it is preferred to sandwich a separator between the positive electrode and the negative electrode. The separator has ion permeability and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0141] As an example of the structure of a secondary battery, an electrode group in which a positive electrode and a negative electrode are wound with a separator and an electrolyte solution is contained in an outer body can be cited. A stacked electrode group in which a positive electrode and a negative electrode are stacked with a separator can also be used. The secondary battery can have a cylindrical, square, coin, button, sheet, and other forms.

[0142] Below, refer to Figure 3 An example of the secondary battery of the present disclosure will be described.

[0143] The battery comprises a battery case 4 with a square bottom, and an electrode group 1 and an electrolyte (not shown) housed in the battery case 4. The electrode group 1 comprises a strip-shaped negative electrode, a strip-shaped positive electrode and a separator therebetween. The negative electrode collector of the negative electrode is electrically connected to a negative terminal 6 provided on a sealing plate 5 via a negative electrode lead 3. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. The positive electrode collector of the positive electrode is electrically connected to the back of the sealing plate 5 via a positive electrode lead 2. That is, the positive electrode is electrically connected to the battery case 4 which also serves as the positive terminal. The periphery of the sealing plate 5 is fitted with the open end of the battery case 4, and the fitting portion is laser welded. There is an injection hole for the electrolyte on the sealing plate 5, which is plugged with a sealing plug 8 after injection.

[0144] Postscript

[0145] The following techniques are disclosed through the description of the above embodiments.

[0146] (Technology 1)

[0147] A negative electrode material for a secondary battery comprises a composite material, wherein the composite material comprises an amorphous material phase and a silicate phase, wherein the silicate phase is dispersed in the amorphous material phase, wherein the amorphous material phase comprises Si, O and C, and wherein the silicate phase contains an element M, wherein the element M is at least one selected from Li, Na, K, Mg, Ca, B and Al.

[0148] (Technique 2)

[0149] According to the negative electrode material for a secondary battery described in the first aspect, in the cross section of the composite material, the amorphous material phase has no substantial grain boundaries.

[0150] (Technique 3)

[0151] According to the negative electrode material for a secondary battery described in technology 1 or 2, the silicate phase and the amorphous material phase each independently contain the element M.

[0152] (Technique 4)

[0153] According to the negative electrode material for a secondary battery described in the third aspect, the amorphous material phase contains at least Li as the element M.

[0154] (Technique 5)

[0155] According to the negative electrode material for a secondary battery as described in any one of techniques 1 to 4, the silicate phase contains at least Li as the element M.

[0156] (Technique 6)

[0157] According to the negative electrode material for a secondary battery described in any one of techniques 1 to 4, the silicate phase contains at least one selected from Li4SiO4, Li2SiO3 and Li2Si2O5.

[0158] (Technique 7)

[0159] According to the negative electrode material for a secondary battery according to any one of techniques 1 to 6, the silicate phase is in a particle form, and the average particle size of the silicate phase is 10 nm or more and 100 μm or less.

[0160] (Technology 8)

[0161] According to the negative electrode material for secondary battery described in technology 3, the amorphous material phase is represented by the general formula: M a SiO x N y C z It means that 0<a≤4, 0.1≤x≤2.5, 0≤y≤0.5, and 0<1-0.5x-0.75y<z≤6.

[0162] (Technique 9)

[0163] According to the negative electrode material for a secondary battery described in the technique 8, in the general formula, M contains at least Li.

[0164] (Technology 10)

[0165] According to the negative electrode material for a secondary battery as described in any one of technologies 1 to 9, the composite material has voids inside the amorphous material phase, and the silicate phase is exposed on the inner wall surface of the voids.

[0166] (Technology 11)

[0167] The negative electrode material for a secondary battery according to any one of techniques 1 to 10 further comprises a conductive layer covering a surface of the composite material, wherein the conductive layer contains a carbon material having conductivity.

[0168] (Technology 12)

[0169] According to the negative electrode material for a secondary battery described in any one of technologies 1 to 11, the composite material further includes an active phase that reacts with Li, and the active phase is dispersed in the amorphous material phase.

[0170] (Technology 13)

[0171] According to the negative electrode material for a secondary battery described in the technique 12, the material constituting the active phase includes at least one selected from metals and intermetallic compounds.

[0172] (Technology 14)

[0173] According to the negative electrode material for secondary batteries recorded in technology 13, the metal is at least one selected from Si, Sn, Ti, Al and Mg, and the intermetallic compound is selected from CrSi2, MnSi2, FeSi2, CoSi2, NiSi2, LiNiSn and M x At least one of Si (M is at least one selected from Li, Na, K, Mg, Ca, B and Al, satisfying 0<x<5).

[0174] (Technology 15)

[0175] According to the secondary battery negative electrode material according to any one of technologies 12 to 14, the content of the active phase in the composite material is 20% by mass or more and 95% by mass or less.

[0176] (Technology 16)

[0177] According to the negative electrode material for a secondary battery described in any one of techniques 12 to 15, the active phase is in a particle form, and the average particle size of the active phase is 1 nm or more and 1000 nm or less.

[0178] (Technology 17)

[0179] The negative electrode material for a secondary battery according to any one of techniques 1 to 16, further comprising at least one selected from graphite, hard carbon and soft carbon.

[0180] (Technology 18)

[0181] A secondary battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises the negative electrode material for a secondary battery as described in any one of techniques 1 to 17.

[0182] (Technology 19)

[0183] A method for manufacturing a negative electrode material for a secondary battery, comprising a step of obtaining a raw material mixture and a step of sintering the raw material mixture to generate a composite material, wherein the raw material mixture comprises a first polymer, a material constituting an active phase that reacts with Li, and a compound containing an element M, wherein the first polymer is an organic silicon polymer containing Si, O, and C, and the composite material comprises an amorphous material phase, the active phase, and a silicate phase, wherein the active phase and the silicate phase are respectively dispersed in the amorphous material phase, wherein the amorphous material phase contains Si, O, and C, and the silicate phase and the amorphous material phase each independently contain the element M, and the element M is at least one selected from Li, Na, K, Mg, Ca, B, and Al.

[0184] (Technology 20)

[0185] According to the method for producing a negative electrode material for a secondary battery described in Technology 19, the silicate phase and the amorphous material phase each contain at least Li as the element M.

[0186] (Technology 21)

[0187] According to the method for producing a negative electrode material for a secondary battery described in technology 19 or 20, the compound containing element M is at least one selected from lithium carbonate, lithium formate, lithium acetate and lithium benzoate.

[0188] (Technology 22)

[0189] According to the method for producing a negative electrode material for a secondary battery as described in any one of techniques 19 to 21, the first polymer is at least one selected from polysiloxane, polycarbosilane and polysilazane.

[0190] (Technology 23)

[0191] According to the method for producing a negative electrode material for a secondary battery described in any one of techniques 19 to 22, in the step of obtaining the raw material mixture, the raw material mixture contains a second polymer, and the second polymer is carbonized together with carbon atoms of the first polymer when the raw material mixture is fired.

[0192] (Technology 24)

[0193] According to the method for producing a negative electrode material for a secondary battery described in technology 23, the second polymer is at least one selected from polyethylene resin, polyimide resin, polyacrylonitrile, acrylic resin and polyolefin resin.

[0194] [Example]

[0195] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0196] 《Example 1》

[0197] As the silicone polymer, a silicone resin (a type containing a solvent) was prepared. Specifically, a product name "KR-112" manufactured by Shin-Etsu Chemical Co., Ltd. (containing an organic solvent (toluene, xylene), non-volatile content (105°C × 3h): 70%, dynamic viscosity (25°C): 200 mm 2 / s).

[0198] As a Li-containing compound, lithium carbonate (Li 2 CO 3 ) powder (the maximum particle diameter is in the range of 1 μm or more and less than 100 μm) was prepared.

[0199] Powdered lithium carbonate was added to "KR-112" and mixed to obtain a uniform paste-like raw material mixture. The mixing was performed by stirring at 20,000 rpm for 3 minutes in an atmosphere at room temperature using a thin film rotary high-speed mixer "Filmix" manufactured by Primix (Co., Ltd.). The amount of lithium carbonate added was adjusted so that the molar ratio of Li from lithium carbonate to Si from silicone resin was Li / Si=1.

[0200] The raw material mixture was transferred to an alumina crucible and fired in a nitrogen atmosphere at 875° C. for 5 hours. The fired product was pulverized using a mortar and passed through a sieve with a mesh size of 75 μm to obtain composite particles (negative electrode material A1).

[0201] The negative electrode material A1 (composite particles) was subjected to SEM-EDX analysis. As a result, in the cross-sectional SEM image of the composite particles, an amorphous material phase and a silicate phase dispersed in the amorphous material phase can be confirmed. It can be confirmed that the composite particles have voids inside the amorphous material phase, and the silicate phase is exposed on the inner wall surface of the void. The amorphous material phase contains Li, Si, O and C. The composition of the silicate phase is mainly Li2SiO3.

[0202] 《Example 2》

[0203] A composite material (negative electrode material A2) was obtained in the same manner as in Example 1 except that the amount of lithium carbonate added was adjusted so that the molar ratio of Li derived from lithium carbonate to Si derived from the silicone resin became Li / Si=0.5.

[0204] Comparative Example 1

[0205] Composite particles (negative electrode material B1) were obtained in the same manner as in Example 1 except that lithium carbonate was not added to “KR-112” (calcination was performed using only “KR-112”).

[0206] The negative electrode material B1 (composite particles) was subjected to SEM-EDX analysis. In the cross-sectional SEM image of the composite particles, an amorphous material phase was confirmed, but a silicate phase dispersed in the amorphous material phase was not confirmed.

[0207] [Evaluation 1]

[0208] For each of the negative electrode materials of Examples 1 to 2 and Comparative Example 1, a test cell including the negative electrode material was prepared in the following order, and the irreversible capacity was determined.

[0209] <Production of test unit>

[0210] (Fabrication of working electrode (negative electrode))

[0211] The negative electrode material, carbon nanotubes (CNT), polyacrylic acid (PAA), styrene-butadiene copolymer rubber (SBR), carboxymethyl cellulose (CMC) and an appropriate amount of water are mixed to prepare a negative electrode slurry. Relative to 100 parts by mass of the negative electrode material, the added amounts of CNT, PAA, CMC and SBR are 0.5 parts by mass, 5 parts by mass, 5 parts by mass and 5 parts by mass, respectively.

[0212] The negative electrode slurry was applied to one side of an electrolytic copper foil as a current collector, punched out into a size of 2 cm×2 cm, and then dried to form a negative electrode mixture layer. In this way, a negative electrode was obtained.

[0213] (Fabrication of Counter Electrode)

[0214] A lithium metal foil was attached to one side of an electrolytic copper foil (current collector) and punched into a square with a side of 2.5 cm to prepare a counter electrode.

[0215] (Preparation of Electrolyte)

[0216] A mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of EC:EMC:DMC=4:1:15 was obtained. LiPF6 was dissolved in the mixed solvent at a concentration of 1.3 mol / L to prepare an electrolyte solution.

[0217] (Assembly of test unit)

[0218] The negative electrode and the counter electrode are arranged opposite to each other through a separator to form an electrode body. A microporous film made of polyolefin is used as the separator. The electrode body is housed in an outer body composed of an aluminum laminate, and after injecting an electrolyte, the opening of the outer body is sealed. At this time, a portion of the lead installed on the negative electrode and the counter electrode is exposed from the outer body respectively. In this way, a test unit is obtained.

[0219] <Charge and discharge test>

[0220] For the test cell, the following charging and discharging were performed in a constant temperature bath at 25° C. The pause time between charging and discharging was 20 minutes.

[0221] (Charge)

[0222] The battery is charged at a constant current of 0.1C (1C is the current value that discharges the designed capacity in 1 hour) until the cell voltage reaches 0.005V. The pause time is 20 minutes. Next, the battery is charged at a constant current of 0.01C until the cell voltage reaches 0.005V. The pause time is 20 minutes. Furthermore, the battery is charged at a constant current of 0.001C until the cell voltage reaches 0.005V.

[0223] (Discharge)

[0224] The battery was discharged at a constant current of 0.1C until the cell voltage reached 1V. The pause time was 20 minutes. Then, the battery was discharged at a constant current of 0.01C until the cell voltage reached 1V. The pause time was 20 minutes. Furthermore, the battery was discharged at a constant current of 0.001C until the cell voltage reached 1V.

[0225] The charge and discharge capacities per unit mass of the negative electrode material (composite particles) were calculated by the above charge and discharge, and the irreversible capacity was calculated as the value obtained by subtracting the discharge capacity from the charge capacity. The irreversible capacity was expressed as a relative value when the irreversible capacity of battery B1 of comparative example 1 was 100.

[0226] The evaluation results are shown in Table 1.

[0227] Table 1

[0228]

[0229] Compared with negative electrode material B1, the irreversible capacities of negative electrode materials A1 and A2 are significantly reduced.

[0230] 《Example 3》

[0231] As the organosilicon polymer, the same organosilicon resin (containing a solvent) as in Example 1 was prepared. As the Li-containing compound, the same lithium carbonate powder as in Example 1 was prepared. As the material constituting the active phase, silicon nanoparticles (average particle size 40 nm) were prepared.

[0232] Lithium carbonate powder and silicon nanoparticles were added to "KR-112" and mixed to obtain a uniform paste-like raw material mixture. The mixing was performed by stirring at 20,000 rpm for 3 minutes in an atmosphere at room temperature using a thin film rotary high-speed mixer "Filmix" manufactured by Primix (Co., Ltd.).

[0233] The amount of lithium carbonate added was adjusted so that the molar ratio of Li derived from lithium carbonate to Si derived from the silicone resin was Li / Si = 1. The amount of silicon nanoparticles added was 11.9 parts by mass based on 100 parts by mass of "KR-112".

[0234] The raw material mixture was transferred to an alumina crucible and fired in a nitrogen atmosphere at 875° C. for 5 hours. The fired product was pulverized using a mortar and passed through a sieve with a mesh size of 75 μm to obtain composite particles (negative electrode material A3).

[0235] The negative electrode material A3 (composite particles) was subjected to SEM-EDX analysis. In the cross-sectional SEM image of the composite particles, an amorphous material phase and a silicate phase and an active phase dispersed in the amorphous material phase can be confirmed. It can be confirmed that there are voids inside the amorphous material phase, and the silicate phase is exposed on the inner wall surface of the void. The amorphous material phase contains Li, Si, O and C. The composition of the silicate phase is mainly Li2SiO3.

[0236] 《Example 4》

[0237] The amount of lithium carbonate added was adjusted so that the molar ratio of Li from lithium carbonate to Si from the silicone resin was Li / Si = 0.5. The amount of silicon nanoparticles added was 11.2 parts by mass relative to 100 parts by mass of "KR-112". Composite particles (negative electrode material A4) were obtained in the same manner as in Example 3 except for the above.

[0238] Comparative Example 2

[0239] No lithium carbonate powder was added to "KR-112". The amount of silicon nanoparticles added was 10.3 parts by mass relative to 100 parts by mass of the silicone resin. Composite particles (negative electrode material B2) were obtained in the same manner as in Example 3 except for the above.

[0240] The negative electrode material B2 (composite particles) was subjected to SEM-EDX analysis. In the cross-sectional SEM image of the composite particles, an amorphous material phase and an active phase dispersed in the amorphous material phase were confirmed, but a silicate phase dispersed in the amorphous material phase was not confirmed.

[0241] [Evaluation 2]

[0242] For the negative electrode materials of Examples 3 to 4 and Comparative Example 2, test cells equipped with negative electrode materials were prepared by the same method as in [Evaluation 1], and the irreversible capacity was obtained by charging and discharging. The irreversible capacity was expressed as a relative value when the irreversible capacity of the battery B2 of Comparative Example 2 was 100. Furthermore, the ratio (percentage) of the discharge capacity to the charge capacity was obtained as the initial charge and discharge efficiency.

[0243] The evaluation results are shown in Table 2.

[0244] Table 2

[0245]

[0246] Compared with negative electrode material B2, the irreversible capacity of negative electrode materials A3 and A4 is greatly reduced, and the charge and discharge efficiency is improved.

[0247] Industrial Availability

[0248] The negative electrode material for a secondary battery according to the present disclosure can be used for a secondary battery used as a main power source for mobile communication devices, portable electronic devices, and the like.

[0249] The present invention has been described in conjunction with the currently preferred embodiments, but this disclosure should not be interpreted as limiting. By reading the above disclosure, a person of ordinary skill in the art to which the present invention belongs can clearly understand various modifications and changes. Therefore, the attached claims should be interpreted as including all modifications and changes without departing from the spirit and scope of the present invention.

[0250] Description of Reference Numerals

[0251] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug, 20: negative electrode material, 21: composite particles, 22: amorphous material phase, 23: active phase, 24: silicate phase, 25: conductive layer, 26: voids

Claims

1. A negative electrode material for a secondary battery, comprising a composite material, The composite material comprises an amorphous material phase and a silicate phase, The silicate phase is dispersed in the amorphous material phase, The amorphous material phase comprises Si, O and C, The silicate phase contains the element M, The element M is at least one selected from Li, Na, K, Mg, Ca, B and Al.

2. The negative electrode material for a secondary battery according to claim 1, In a cross section of the composite material, the amorphous material phase has no substantial grain boundaries.

3. The negative electrode material for a secondary battery according to claim 1, The silicate phase and the amorphous material phase each independently contain the element M.

4. The negative electrode material for a secondary battery according to claim 3, The amorphous material phase contains at least Li as the element M.

5. The negative electrode material for a secondary battery according to claim 1, The silicate phase contains at least Li as the element M.

6. The negative electrode material for a secondary battery according to claim 1, The silicate phase comprises at least one selected from Li4SiO4, Li2SiO3 and Li2Si2O5.

7. The negative electrode material for a secondary battery according to claim 1, The silicate phase is in particle form, The average particle size of the silicate phase is 10 nm or more and 100 μm or less.

8. The negative electrode material for a secondary battery according to claim 3, The amorphous material phase is represented by the general formula: M a SiO x N y C z express, It satisfies 0<a≤4, 0.1≤x≤2.5, 0≤y≤0.5, and 0<1-0.5x-0.75y<z≤6.

9. The negative electrode material for a secondary battery according to claim 8, In the general formula, M contains at least Li.

10. The negative electrode material for a secondary battery according to claim 1, The composite material has voids inside the amorphous material phase, The silicate phase is exposed on the inner wall surface of the void.

11. The negative electrode material for a secondary battery according to claim 1, further comprising a conductive layer covering the surface of the composite material, The conductive layer includes a carbon material having electrical conductivity.

12. The negative electrode material for a secondary battery according to claim 1, The composite material also comprises an active phase that reacts with Li, The active phase is dispersed within the amorphous material phase.

13. The negative electrode material for a secondary battery according to claim 12, The material constituting the active phase includes at least one selected from metals and intermetallic compounds.

14. The negative electrode material for a secondary battery according to claim 13, The metal is at least one selected from Si, Sn, Ti, Al and Mg, The intermetallic compound is selected from CrSi2, MnSi2, FeSi2, CoSi2, NiSi2, LiNiSn and M x At least one of Si, M is at least one selected from Li, Na, K, Mg, Ca, B and Al, and 0<x<5.

15. The negative electrode material for a secondary battery according to claim 12, The content of the active phase in the composite material is 20 mass % or more and 95 mass % or less.

16. The negative electrode material for a secondary battery according to claim 12, The active phase is in the form of particles, The average particle size of the active phase is greater than or equal to 1 nm and less than or equal to 1000 nm.

17. The negative electrode material for a secondary battery according to claim 1, The invention further comprises at least one selected from graphite, hard carbon and soft carbon.

18. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte. The negative electrode comprises the negative electrode material for a secondary battery according to claim 1 .

19. A method for producing a negative electrode material for a secondary battery, comprising the steps of obtaining a raw material mixture and firing the raw material mixture to generate a composite material, The raw material mixture includes a first polymer, a material constituting an active phase that reacts with Li, and a compound containing an element M, wherein the first polymer is an organic silicon polymer containing Si, O, and C. The composite material comprises an amorphous material phase, the active phase and a silicate phase, The active phase and the silicate phase are respectively dispersed in the amorphous material phase, The amorphous material phase comprises Si, O and C, The silicate phase and the amorphous material phase each independently contain the element M, The element M is at least one selected from Li, Na, K, Mg, Ca, B and Al.

20. The method for producing a negative electrode material for a secondary battery according to claim 19, The silicate phase and the amorphous material phase each contain at least Li as the element M.

21. The method for producing a negative electrode material for a secondary battery according to claim 19, The compound containing the element M is at least one selected from lithium carbonate, lithium formate, lithium acetate and lithium benzoate.

22. The method for producing a negative electrode material for a secondary battery according to claim 19, The first polymer is at least one selected from polysiloxane, polycarbosilane and polysilazane.

23. The method for producing a negative electrode material for a secondary battery according to claim 19, In the step of obtaining the raw material mixture, the raw material mixture includes a second polymer, and the second polymer is carbonized together with carbon atoms of the first polymer when the raw material mixture is fired.

24. The method for producing a negative electrode material for a secondary battery according to claim 23, The second polymer is at least one selected from polyethylene resin, polyimide resin, polyacrylonitrile, acrylic resin and polyolefin resin.

Citation Information

Patent Citations

  • Si-C-O AMORPHOUS MATERIAL AND NEGATIVE ELECTRODE FOR LITHIUM SECONDARY BATTERY USING THE MATERIAL

    JP2007115548A